Tertiary bioreceptivity of schists from prehistoric rock art sites in the Côa Valley (Portugal) and Siega Verde (Spain) archaeological parks: Effects of cleaning treatments. (August 2019) - Sanmartín, P.; Fuentes, E.; Montojo, C.; Barreiro, P.; Paz-Bermúdez, G.; Prieto, B.
Abstract: Schist weathering induced by the presence of lichen is one of the main concerns in the Côa Valley (northeast Portugal) and Siega Verde (northwest Spain) Archaeological Parks. In this study, different types of lichens, including mainly crustose forms ( Caloplaca pellodella, Candelariella vitellina, Circinaria hoffmanniana, Diploschistes actinostomus and Lecidea fuscoatra ) as well as some foliose forms ( Parmelina tiliacea and Xanthoparmelia conspersa ), were removed from schistose samples of both lithotypes in different locations. The lichens were removed by treatment with Biotin T ® biocide or by laser treatment with the first (1064 nm, IR) and fourth (266 nm, UV) harmonics of a Nd:YAG laser. To assess the effects of the treatments, a recolonization experiment was carried out with biofilm-forming phototrophic microorganisms, and a bioreceptivity index (BI) was calculated for each lithotype and treatment. A water-based treatment (the removal method currently used in both parks) was used as a control cleaning treatment in the bioreceptivity experiment. The study findings show the importance of bioreceptivity studies for evaluating the effectiveness of cleaning treatments. Treatment of the schist samples with the chemical biocide significantly decreased the bioreceptivity (complete inhibition of biofilm formation), whereas laser treatments (especially IR laser) significantly increased the tertiary bioreceptivity. Moreover, the tertiary bioreceptivity of the schists depended on both the treatment applied and the nature of the substrate. Highlights: Methods of removing lichens from schists were tested in two archaeological parks. Water, Biotin T ®, IR laser and UV laser-based treatments were compared. Tertiary bioreceptivity depended on the cleaning treatment used. Biotin T ® completely inhibited biofilm formation. IR laser, and to a lesser extent UV laser, increased the bioreceptivity.